Flame-resistant laminated molding
Patent Information
- Application Number
- JP2020555075
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-10
- Filing Date
- 2020-10-02
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2040-10-02
Smart Images

Figure 0007635551000002 
Figure 0007635551000003 
Figure 0007635551000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a flame-resistant laminated molding, and more particularly to a flame-resistant laminated molding in which a specific fiber sheet material is provided on the outer surface of a resin molded body so that the surface of the molded body has high flame resistance. [Background technology]
[0002] Resin molded articles are used in various fields from the viewpoints of light weight, excellent moldability into a predetermined shape, etc., but depending on the application, high flame retardancy, flame resistance, and even flame shielding may be required. In particular, high flame retardancy, flame resistance, and even flame shielding may be required mainly on the surface or surface layer of the resin molded article.
[0003] Methods for imparting flame retardancy to a resin molded body itself include kneading a chemical having a flame retardant effect into the resin, but the degree of flame retardancy that can be imparted to the molded body using such methods is limited, and it is particularly difficult to impart high flame resistance or flame blocking properties to the molded body itself.
[0004] On the other hand, as nonwoven fabrics and fiber papers, for example, nonwoven fabrics (for example, Patent Document 1) and papers (for example, Patent Document 2) made of a composite of non-melting fibers (for example, flame-resistant yarn) and fibers made of polyphenylene sulfide or the like as a polymer having high flame retardancy are known. Although such nonwoven fabrics and papers themselves can exhibit high flame resistance and flame blocking properties, it is difficult to form a molded body having the desired strength and rigidity with the nonwoven fabric or paper itself, and even if it is possible to mold it, it is necessary to make the nonwoven fabric or paper considerably thick, so that it is likely to be extremely expensive. In addition, it is difficult to ensure good moldability. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-169996 A [Patent Document 2] WO 2017 / 6807 Summary of the Invention [Problem to be solved by the invention]
[0006] In view of the above-mentioned circumstances, an object of the present invention is to provide a flame-resistant laminated molded body that can exhibit the high flame resistance and flame shielding properties required for the surface or surface layer of a resin molded body, and can easily ensure the desired strength and rigidity required for the molded body as a whole, as well as good moldability into a desired shape. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention employs the following means. (1) A flame-resistant laminated molded body in which one side of a fiber sheet material containing at least non-melting fibers A is exposed to the outside of the molded body, and at least a portion of the other side is bonded to a thermoplastic resin C that constitutes the main body of the molded body. (2) The flame-resistant laminated molding according to (1), wherein the fiber sheet material contains the non-melting fiber A and the thermoplastic fiber B. (3) The flame-resistant laminate according to (1) or (2), wherein the non-melting fiber A has a thermal conductivity of 0.060 W / m·K or less as determined by ISO 22007-3 (2008). (4) The flame-resistant laminated molding according to any one of (1) to (3), wherein the content of the non-melting fiber A in the fiber sheet material is 15 to 80% by weight. (5) The flame-resistant laminated molding according to any one of (2) to (4), wherein the content of the thermoplastic fiber B in the fiber sheet material is 20 to 85% by weight. (6) The flame-resistant laminated molding according to any one of (2) to (5), wherein the fiber sheet material contains fibers D other than the non-melting fibers A and the thermoplastic fibers B in an amount of 20% by weight or less. (7) The flame-resistant laminated molding according to any one of (1) to (6), wherein the non-melting fiber A is a flame-resistant fiber or a meta-aramid fiber. (8) The flame-resistant laminated molding according to any one of (2) to (7), wherein the thermoplastic fiber B has an LOI value of 25 or more according to JIS K 7201-2 (2007). (9) The flame-resistant laminate molding according to any one of (2) to (8), wherein the thermoplastic fiber B is a fiber made of a resin selected from the group consisting of anisotropic melt polyester, liquid crystal polyester, flame-retardant poly(butylene terephthalate), poly(acrylonitrile butadiene styrene), flame-retardant polysulfone, poly(ether-ether-ketone), poly(ether-ketone-ketone), polyethersulfone, polyarylate, polyarylene sulfide, polyphenylsulfone, polyetherimide, polyamideimide, and mixtures thereof. (10) The flame-resistant laminated molding according to any one of (2) to (9), wherein the thermoplastic fiber B is a fiber containing 15% by weight or more of sulfur atoms. (11) The flame-resistant laminate molding according to any one of (1) to (10), wherein the thermoplastic resin C has an LOI value of 25 or more as measured in accordance with JIS K 7201-2 (2007). (12) The flame-resistant laminate molding according to any one of (1) to (11), wherein the thermoplastic resin C is a resin selected from the group consisting of anisotropic melt polyester, liquid crystal polyester, flame-retardant polyamide 66, flame-retardant poly(butylene terephthalate), poly(acrylonitrile butadiene styrene), flame-retardant polysulfone, poly(ether-ether-ketone), poly(ether-ketone-ketone), polyethersulfone, polyarylate, polyarylene sulfide, polyphenylsulfone, polyetherimide, polyamideimide, and mixtures thereof. (13) The flame-resistant laminated molding according to any one of (2) to (12), wherein a part of the thermoplastic fibers B and a part of the thermoplastic resin C are fused to each other. (14) The thermoplastic fiber B and the thermoplastic resin C are made of the same resin, and the bonding strength between the fiber sheet material containing the non-melting fiber A and the thermoplastic fiber B and the thermoplastic resin C is 1.5 kg / cm 2 The flame-resistant laminated molding according to any one of (2) to (13) above. (15) The flame-resistant laminated molding according to any one of (2) to (14), wherein the fiber sheet material containing the non-melting fiber A and the thermoplastic fiber B is configured as a fiber sheet material capable of exhibiting flame-proofing properties by forming a membrane between the non-melting fiber A by melting the thermoplastic fiber B and carbonizing the membrane in the absence of oxygen. (16) The flame-resistant laminated molding according to any one of (2) to (15), wherein a fiber sheet material containing the non-melting fiber A and the thermoplastic fiber B is heat-fused to the thermoplastic resin C, and a fused compatible layer between the thermoplastic fiber B and the thermoplastic resin C has a thickness of 10 μm or more. (17) The flame-resistant laminated molding according to any one of (1) to (16), wherein the fiber sheet material containing the non-melting fibers A is partially present on a surface of the thermoplastic resin C. Effect of the Invention
[0008] According to the flame-resistant laminated molding of the present invention as described above, the fiber sheet material containing the non-melting fiber A itself can exhibit high flame resistance and flame shielding due to the presence of the non-melting fiber A, but since one side of the fiber sheet material is bonded to the molded body composed of the thermoplastic resin C in a state where it is exposed to the outside, the surface part of the laminated molding as a whole can efficiently exhibit high flame resistance and flame shielding. At the same time, since the molded body can be easily molded into a desired shape by substantially any molding method using the thermoplastic resin C, the laminated molding as a whole can be easily formed into a desired shape at a low cost and with good moldability while ensuring the desired strength and rigidity due to the molded body. Therefore, it is possible to realize the expression of the required high flame resistance and flame shielding as a flame-resistant laminated molding, and the securing of the required overall desired strength, rigidity, and good moldability. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a perspective view showing an example of a test piece of the flame-resistant laminated molding according to the present invention. [Diagram 2] FIG. 2 is a perspective view showing a test piece for measuring bonding strength in a flame-resistant laminated molding. [Diagram 3]FIG. 1 is a perspective view showing an example of a battery module loading pack as one embodiment of a flame-resistant laminate according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The flame-resistant laminated molded body of the present invention is characterized in that one side of a fiber sheet material containing at least non-melting fiber A is exposed to the outside of the molded body, and at least a portion of the other side is bonded to thermoplastic resin C that constitutes the main body of the molded body.
[0011] As the fiber sheet material containing at least the non-melting fiber A, woven fabric, knitted fabric, felt, paper, etc. can be used, and short fibers and long fibers processed by a known method can be used. Among them, nonwoven fabric is preferable from the viewpoint of flame resistance. In addition, the thickness of the fiber sheet material is not particularly limited, but is preferably 0.05 to 10 mm from the viewpoint of reducing the weight, reducing the cost, and improving the performance of the laminated molded product.
[0012] The non-melting fiber A in the present invention refers to a fiber that does not liquefy when exposed to flame and maintains its fiber shape, and is preferably one that does not liquefy or ignite at a temperature of 800°C, and more preferably one that does not liquefy or ignite at a temperature of 1000°C or higher. Examples of such non-melting fiber A include flame-resistant fiber, meta-aramid fiber, and glass fiber. The flame-resistant fiber is a fiber that is flame-resistant treated using a fiber selected from acrylonitrile-based, pitch-based, cellulose-based, and phenol-based fibers as a raw material. These may be used alone or two or more types may be used simultaneously. Among them, flame-resistant fibers that have a low high-temperature shrinkage rate and further improve heat resistance at high temperatures due to the oxygen blocking effect of the film formed by the thermoplastic fiber B described below when exposed to flame, which progresses carbonization, are preferred. Among various flame-resistant fibers, acrylonitrile-based flame-resistant fibers are more preferably used as fibers that have a low specific gravity, are flexible, and have excellent flame retardancy, and such flame-resistant fibers are obtained by heating and oxidizing an acrylic fiber as a precursor in high-temperature air. Examples of commercially available products include the flame-retardant fiber PYRON (registered trademark) manufactured by Zoltek, which was used in the Examples and Comparative Examples described later, as well as Pyromex (registered trademark) manufactured by Toho Tenax Co., Ltd. Here, the high temperature shrinkage rate is a value calculated by the following formula from L0 and L1, after leaving the fiber under standard conditions (20°C, relative humidity 65%) for 12 hours, applying a tension of 0.1 cN / dtex to measure the original length L0, exposing the fiber to a dry heat atmosphere at 290°C for 30 minutes without applying a load, sufficiently cooling the fiber under standard conditions (20°C, relative humidity 65%), and then applying a tension of 0.1 cN / dtex to measure the length L1. High temperature shrinkage rate = [(L0-L1) / L0] x 100 (%)
[0013] The non-melting fiber A in the present invention preferably has a thermal conductivity of 0.060 W / m K or less, measured by a method conforming to ISO22007-3 (2008). Thermal conductivity is a numerical expression of the ease of heat conduction, and low thermal conductivity means that when a material is heated from one side, the temperature rise in the unheated part is small. 2, the thickness measured by a method conforming to JIS L1913 (2010) is 2 mm (density 100 kg / m 3 A material with a thermal conductivity of 0.060 W / m K or less, measured using a method conforming to ISO 22007-3 (2008) using felt of the same material as the test specimen, is less likely to transmit heat, and when made into a nonwoven fabric and heated from one side, it is possible to suppress the temperature rise on the unheated opposite side, reducing the possibility of the combustible material catching fire even if it is placed on the opposite side. A lower thermal conductivity is preferable, but the lower limit for available fiber materials is around 0.020 W / m K.
[0014] The non-melting fiber A preferably used in the present invention is preferably used alone or in combination with a different material, and it is preferable to use the non-melting fiber A in combination with a thermoplastic resin B.
[0015] The thermoplastic fiber B in the present invention preferably has an LOI (Limiting Oxygen Index) value of 25 or more according to JIS K7201-2 (2007). The LOI value is the volume percentage of the minimum amount of oxygen required to sustain the combustion of a substance in a mixed gas of nitrogen and oxygen, and it can be said that the higher the LOI value, the more difficult it is to burn. Therefore, a thermoplastic fiber having an LOI value of 25 or more according to JIS K7201-2 (2007) is difficult to burn, and even if it ignites, it will immediately extinguish if the source of fire is removed, and usually forms a carbonized film on the part where the fire spreads slightly, and this carbonized part can prevent the fire from spreading. The higher the LOI value, the more preferable it is, but the upper limit of the LOI value of a substance that is actually available is about 65.
[0016] Specific examples of the thermoplastic fiber B in the present invention include fibers composed of a thermoplastic resin selected from the group consisting of anisotropic melt polyester, liquid crystal polyester, flame-retardant poly(butylene terephthalate), poly(acrylonitrile butadiene styrene), flame-retardant polysulfone, poly(ether-ether-ketone), poly(ether-ketone-ketone), polyethersulfone, polyarylate, polyarylene sulfide, polyphenylsulfone, polyetherimide, polyamideimide, and mixtures thereof. These may be used alone or two or more may be used simultaneously. When the LOI value is within the preferred range of the present invention, combustion in air is suppressed and the thermoplastic resin is easily carbonized. In addition, when the melting point is lower than the ignition temperature of the non-melting fiber A, the molten thermoplastic resin forms a film on the surface of the non-melting fiber A and between the fibers, and when the film is carbonized, the effect of blocking oxygen is enhanced, and the oxidative deterioration of the non-melting fiber A can be suppressed, and the carbonized film exhibits excellent flame-shielding properties. The melting point of the thermoplastic fiber B is preferably at least 200°C lower than the ignition temperature of the non-melting fiber A, and more preferably at least 300°C lower. Among these, polyphenylene sulfide fiber (hereinafter sometimes referred to as PPS fiber) is most preferred in terms of the high LOI value, the range of the melting point, and the ease of availability. In addition, even if the thermoplastic resin has an LOI value that is not within the range specified in the present invention, it can be preferably used as long as the LOI value after treatment with a flame retardant is within the range specified in the present invention.
[0017] The PPS fiber preferably used in the present invention is a synthetic fiber made of a polymer containing -(C6H4-S)- as a main structural unit. Representative examples of PPS fibers containing the above structural unit include polyphenylene sulfide (hereinafter sometimes referred to as PPS), polyphenylene sulfide sulfone, polyphenylene sulfide ketone, their random copolymers, block copolymers, and mixtures thereof. Particularly preferred PPS fibers are polyphenylene sulfide containing p-phenylene sulfide units represented by -(C6H4-S)- as the main structural unit of the polymer, preferably at 90 mol % or more. PPS fibers made of polyphenylene sulfide containing p-phenylene sulfide units at 80 wt %, and further preferably at 90 wt % or more.
[0018] By including sulfur atoms in the structure of the thermoplastic resin constituting the thermoplastic fiber B or in the flame retardant blended as an additive to the thermoplastic resin, sulfuric acid is generated during thermal decomposition of the polymer or the flame retardant, and a mechanism for dehydrating and carbonizing the polymer substrate can be realized. From the viewpoint of including sulfur atoms, PPS fiber is the most preferable as the thermoplastic fiber B. In addition, when a flame retardant is used, a sulfur-based flame retardant is preferable. It is preferable to use a fiber containing 15% by weight or more of sulfur atoms as the thermoplastic fiber B. Specifically, PPS and polyester to which a sulfur-based flame retardant is added can be mentioned. The upper limit of the ratio of sulfur atoms is preferably 50% by weight or less from the viewpoint of fiber strength. The ratio of sulfur atoms referred to here is obtained by oxidatively decomposing the thermoplastic fiber by using a thermogravimetric analyzer to raise the temperature of about 10 mg of a sample from room temperature to 800 ° C. at 10 ° C. / min under air flow conditions, and quantitatively analyzing the sulfur oxides in the decomposition gas by gas chromatography.
[0019] The fiber sheet material in the present invention preferably contains non-melting fiber A and thermoplastic fiber B. If the mixing ratio of thermoplastic fiber B in the fiber sheet material is too low, the thermoplastic fiber B will not spread sufficiently in a film shape between the non-melting fibers A of the aggregate, so the mixing ratio of thermoplastic fiber B in the fiber sheet material is preferably 20% by weight or more, and more preferably 30% by weight or more. If the mixing ratio of thermoplastic fiber B is too high, the carbonized part will easily become brittle when exposed to flame, and the flame shielding properties will decrease, so the upper limit is preferably 85% by weight or less, and more preferably 75% by weight or less.
[0020] The fiber sheet material in the present invention may contain fiber D other than the non-melting fiber A and the thermoplastic fiber B in order to further impart a specific performance to the fiber sheet material. For example, vinylon fiber, polyester fiber other than the thermoplastic fiber B, nylon fiber, etc. may be used in order to improve moisture absorption and water absorption. The blending ratio of fiber D is not particularly limited as long as it does not impair the effects of the present invention, but it is preferable that the blending ratio of fiber D other than the non-melting fiber A and the thermoplastic fiber B is 20% by weight or less, and more preferably 15% by weight or less. The lower limit of fiber D is not particularly limited as long as the desired performance is imparted, but it is usually preferably about 10% by weight.
[0021] The thermoplastic resin C constituting the molded body of the flame-resistant laminated molded body of the present invention preferably has an LOI value of 25 or more according to JIS K7201-2 (2007). The LOI value is the volume percentage of the minimum amount of oxygen required to sustain the combustion of a substance in a mixed gas of nitrogen and oxygen, and it can be said that the higher the LOI value, the more difficult it is to burn. Therefore, a thermoplastic resin having an LOI value of 25 or more according to JIS K7201-2 (2007) is difficult to burn, and even if it ignites, it will immediately extinguish if the source of fire is removed, and a charred film is usually formed in the part where the fire has spread slightly, and this charred part can prevent the fire from spreading. The higher the LOI value, the more preferable it is, but the upper limit of the LOI value of a substance that is actually available is about 65.
[0022] Specific examples of the thermoplastic resin C in the present invention are preferably thermoplastic resins selected from the group consisting of anisotropic melt polyester, liquid crystal polyester, flame-retardant polyamide 66, flame-retardant poly(butylene terephthalate), poly(acrylonitrile butadiene styrene), flame-retardant polysulfone, poly(ether-ether-ketone), poly(ether-ketone-ketone), polyethersulfone, polyarylate, polyarylene sulfide, polyphenylsulfone, polyetherimide, polyamideimide, and mixtures thereof. These may be used alone or in combination.
[0023] The polyphenylene sulfide resin (hereinafter sometimes referred to as PPS resin) preferably used in the present invention is a polymer having -(C6H4-S)- as the main structural unit. Representative examples of these PPS resins include polyphenylene sulfide, polyphenylene sulfide sulfone, polyphenylene sulfide ketone, their random copolymers, block copolymers, and mixtures thereof. Particularly preferred PPS resins are polyphenylene sulfide resins containing p-phenylene sulfide units represented by -(C6H4-S)- as the main structural unit of the polymer, preferably at 90 mol % or more. Polyphenylene sulfide resins containing p-phenylene sulfide units at 80 wt %, and further preferably at 90 wt % or more are preferred.
[0024] The thermoplastic resin C constituting the molded body of the flame-resistant laminated molded body of the present invention may contain various additives such as the above-mentioned sulfur-based flame retardant, reinforcing fibers such as carbon fiber and glass fiber, flame retardants other than sulfur-based flame retardants, antioxidants, heat stabilizers, ultraviolet absorbers, lubricants, colorants, or crystallization accelerators, within the scope of the present invention. In particular, from the viewpoint of the strength and rigidity of the laminated molded body, it is preferable to blend reinforcing fibers such as carbon fiber and glass fiber. These additives may be used alone or in combination.
[0025] The flame-resistant laminated molded body of the present invention is characterized in that one surface of the fiber sheet material is exposed to the outside of the molded body, and at least a part of the other surface side is bonded to the thermoplastic resin C constituting the molded body. Methods for bonding the fiber sheet material and the thermoplastic resin C to produce a laminated molded body include methods such as heat pressing, vibration welding, and laser welding, and a method using injection molding. Specifically, a method in which a fiber sheet material and a molded body containing thermoplastic resin C are loaded into a heat press device and bonded by applying pressure while applying heat, a method in which a fiber sheet material is placed on a thermoplastic resin molded body and partially melt-welded using a heater heat source, a high-energy density heat source such as an electron beam or a laser beam, or a heat source induced by high frequency or electromagnetic waves, a method in which a fiber sheet material is placed in a mold in advance, and the thermoplastic resin C is filled in the mold and injection molded, etc. are included. Among these, the injection molding method is preferable from the viewpoint of bonding strength and production cost.
[0026] In particular, when the fiber sheet material contains thermoplastic fiber B, it is preferable that a part of the thermoplastic resin B and a part of the thermoplastic resin C constituting the molded body are fused together. By fusing them together, the bonding strength between the fiber sheet substrate and the molded body can be improved.
[0027] Furthermore, in the flame-resistant laminated molding of the present invention, it is preferable that the thermoplastic fiber B and the thermoplastic resin C are the same resin. By using the same resin, the compatibility of the thermoplastic fiber B and the thermoplastic resin C is increased when they are melted, and the bonding strength between the fiber sheet material containing the thermoplastic resin B and the thermoplastic resin C is increased. In the present invention, the bonding strength is 1.5 kg / cm 2 It is preferable that the bonding strength is 1.5 kg / cm or more. 2 As a result of the above, even when the flame-resistant laminated molded body is exposed to flame, the fiber sheet material and the molded body will not separate, and the laminated molded body will not peel off due to the difference in shrinkage between the fiber sheet material and the thermoplastic resin C caused by temperature changes in the environment in which it is used, and sufficient flame resistance can be achieved.
[0028] In the flame-resistant laminated molding of the present invention, when the fiber sheet material is a fiber sheet material containing non-melting fiber A and thermoplastic fiber B, the mechanism by which the particularly excellent flame-blocking properties are exhibited is as follows. When the fiber sheet material containing non-melting fiber A and thermoplastic fiber B comes into contact with flame, the thermoplastic fiber B melts and forms a film so as to fill the spaces between the non-melting fiber A. The film-forming thermoplastic resin B blocks contact between the non-melting fiber A and oxygen, and as a result, the non-melting fiber A is carbonized. The carbonized film thus completed exhibits flame-blocking properties.
[0029] In the flame-resistant laminated molding of the present invention, when the fiber sheet material is a fiber sheet material containing non-melting fiber A and thermoplastic fiber B, the thickness of the fused compatible layer between the thermoplastic fiber B and the thermoplastic resin C formed by thermal fusion of the fiber sheet material and the thermoplastic resin C is preferably 10 μm or more. By making the thickness of the fused compatible layer 10 μm or more, the fiber sheet material and the molded body are not separated even when the flame-resistant laminated molding is exposed to flame, and the fiber sheet material and the thermoplastic resin C are not peeled off due to the shrinkage difference caused by temperature changes in the environment in which the laminated molding is used, and a sufficient flame-resistant effect can be exhibited.
[0030] The thickness of the fused compatible layer can be determined by the following method. After cutting a laminated molded body consisting of a fiber sheet material and a thermoplastic resin C to a predetermined size, a cross section is observed at a magnification of 200 times using a scanning electron microscope (manufactured by JEOL Ltd.) with backscattered radiation. The observation width is about 600 μm, and at five cross-sectional positions at equal intervals of 100 μm excluding both ends, the distance from the surface of the laminated molded body where the fiber sheet material is partially present to the furthest non-melted fiber A and the distance from the surface of the laminated molded body to the furthest unfused interface between the thermoplastic fiber B and the thermoplastic resin C are measured, and the value obtained by subtracting the former distance from the latter distance is regarded as the thickness of the fused compatible layer, and the average value of the five cross-sectional positions is determined.
[0031] The flame-resistant laminated molding of the present invention is in a state where the fiber sheet material is at least partially present on the surface of the thermoplastic resin C. With regard to the flame-resistant effect, the flame-resistant and flame-resistant effects are exhibited when a flame is applied to the fiber sheet material from the side where the fiber sheet material is present. That is, the flame-resistant laminated molding is in a shape where the fiber sheet material is present in the part that comes into direct contact with the flame. In the present invention, the flame-resistant property means that the flame is effectively blocked, and the flame resistance means that even if the product ignites, the product does not raise a flame and the combustion does not continue.
[0032] The flame-resistant laminated molded body of the present invention can be applied to the fields of housing facilities, aircraft, automobiles, etc., taking advantage of its high flame-shielding and flame-resistant properties. In particular, it is useful for application to battery module loading packs that are mounted on xEV automobiles (electric vehicles) and for which flame-resistant standards are set by national regulations from the viewpoint of safety.
[0033] An example of a battery module stacking pack as an embodiment of the flame-resistant laminate according to the present invention is shown in Fig. 3. A battery module stacking pack 5, in which a plurality of battery modules 6 are housed, is composed of the flame-resistant laminate 7 according to the present invention, which is made of the above-mentioned fiber sheet material and thermoplastic resin C. EXAMPLES
[0034] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the descriptions of these examples. First, the materials used in the examples and the methods for evaluating the respective properties will be described.
[0035] (1) Evaluation method for fiber sheet materials [Metaku] The weight of a 30 cm square sample was measured and 2 Weight per unit (g / m 2 ) is expressed as
[0036] Thickness Measurements were taken in accordance with JIS L-1913 (2010).
[0037] (2) Non-melting fiber A <Flame-retardant fiber 7dtex Zoltek's flame-retardant fiber PYRON (registered trademark) cut to 51 mm was used. When heated by a method compliant with JIS K7193 (2010), ignition was not observed even at 1000 °C, and the ignition temperature was 1000 °C or higher. Also, the thermal conductivity was 0.042 W / m·K.
[0038] <Carbon fiber “Torayca” (registered trademark) made by Toray Industries, Inc. with a diameter of 30 microns cut to 51 mm was used. The thermal conductivity was 8.4 W / m·K.
[0039] (3) Thermoplastic fiber B <Stretched yarn of PPS fiber As the stretched PPS fiber, “Turcon” (registered trademark) made by Toray Industries, Inc. with a single fiber fineness of 2.2 dtex (diameter 14 μm) and a cut length of 51 mm, product number S371 was used. The LOI value of this PPS fiber was 34. The ratio of sulfur atoms in the fiber was 26.2% by weight.
[0040] (4) Thermoplastic resin C <Glass fiber-reinforced PPS resin “Torelina” (registered trademark) product number A504-X90B made by Toray Industries, Inc. was used. The LOI value of this PPS resin was 47.
[0041] <Glass fiber-reinforced flame-retardant PBT resin “Turcon” (registered trademark) product number 1184G-A30N made by Toray Industries, Inc. was used. The LOI value of this PBT resin was 32.
[0042] <Glass fiber-reinforced polyamide 6 resin A molded body main body was obtained using glass fiber-reinforced polyamide 6 resin (“Amilan” (registered trademark) product number CM1011G-30B2 made by Toray Industries, Inc.). The LOI value of this polyamide resin was 24.
[0043] (5) Preparation of fiber sheet material The flame-retardant yarn and the drawn PPS fiber yarn were mixed in a fiber spreader, then further mixed in a cotton-blending machine, and then passed through a carding machine to produce a web. The obtained web was laminated in a cross-wrap machine and then felted in a water-entanglement machine to obtain a nonwoven fabric consisting of the drawn PPS fiber yarn and the flame-retardant yarn.
[0044] (6) Preparation of flame-resistant laminated body The above fiber sheet material and thermoplastic resin C were hot pressed under the following conditions using a simple tabletop hot press machine (manufactured by Imoto Machinery Co., Ltd.) to obtain a flame-resistant laminated molded product of the present invention. The fiber sheet material was cut into square shapes of 80 mm length x 80 mm width and strip shapes of 80 mm length x 20 mm width, and then glass fiber reinforced PPS resin was used to produce flat plates of 80 mm length x 80 mm width x 3 mm thickness using an injection molding machine (SE100D, manufactured by Sumitomo Heavy Industries, Ltd.) under conditions of a cylinder temperature of 320° C. and a mold temperature of 150° C. Furthermore, strip-shaped flat plates of 80 mm length x 20 mm width x 3 mm thickness were also produced by cutting from the flat plates. The conditions of the simple benchtop hot press were set to 320°C, which is also the injection molding temperature of PPS, and the material was preheated under pressure at a gauge pressure of 10 kN for 30 seconds. After releasing the pressure of the simple benchtop hot press, a square-shaped fiber sheet material with a length of 80 mm and a width of 80 mm was placed on a glass fiber reinforced PPS resin plate (a plate with a length of 80 mm, a width of 80 mm, and a thickness of 3 mm). The material was then pressed again at a gauge pressure of 10 kN for 30 seconds to be integrated (hereinafter, this joining method may be referred to as the hot press joining method). As shown in Figure 1, a test piece of a flame-resistant laminate molded body with a thickness of 3 mm for flame resistance evaluation was obtained, which was made by overlapping a fiber sheet material (1) with a length of 80 mm and a width of 80 mm and a thermoplastic resin C (2). Under similar conditions, as shown in FIG. 2, a test piece for measuring the bonding strength of a flame-resistant laminated molding in the shape of a strip of 150 mm in length and 20 mm in width was obtained by integrating a glass fiber reinforced PPS resin flat plate (a strip-shaped flat plate of 80 mm in length, 20 mm in width, and 3 mm in thickness) [thermoplastic resin C(4)] and a strip-shaped fiber sheet material 3 of 80 mm in length and 20 mm in width with their ends overlapped by 10 mm.
[0045] (7) Evaluation method for flame-resistant laminated molded products <Flame resistance test method> The fiber sheet surface of the laminated molded body (flame resistance evaluation test piece) shown in Figure 1 was exposed to flame for 2 minutes under flame exposure conditions conforming to UL94 5V using a burner (burner angle 20±5°, methane gas flow rate 965±30 ml, flame height 125±10 mm, internal blue flame height 40±2 mm). During flame exposure, the presence or absence of flame penetration and ignition was visually confirmed, and 2 minutes after flame exposure, the temperature of the center of the thermoplastic resin C surface on the side opposite the flame was measured with a non-contact thermometer (FLIR: product number CPA-0130A). After flame exposure was completed, the appearance of the fiber sheet surface, the appearance of the thermoplastic resin C surface on the side opposite the flame, and the internal condition of the joint surface were confirmed.
[0046] <Bonding strength test method> Using the laminated molded body (bonding strength test piece) shown in FIG. 2, a tensile test was performed with a tensile tester (AG-500C, manufactured by Shimadzu Corporation) at a chuck distance of 50 mm and a tensile speed of 5 mm / min, and the average of five samples was taken as the bonding strength.
[0047] [Example 1] As a fiber sheet material, a nonwoven fabric was obtained with a weight ratio of 60:40 of drawn PPS fiber yarn and flame-resistant yarn. The basis weight was 100 g / m 2 The nonwoven fabric and the glass fiber reinforced PPS resin were integrated by hot press bonding to obtain a flame-resistant laminated molded article. The obtained flame-resistant laminated molded article had a fusion compatible layer thickness of 70 μm and a bonding strength of 4.3 kg / cm in a tensile test. 2 The failure mode after the tensile test was failure of the nonwoven fabric base material, a good result. In the flame resistance test, there was no penetration of the flame or ignition of the glass fiber reinforced PPS resin, and the maximum temperature at the center of the surface of the glass fiber reinforced PPS resin on the non-flame side was 188°C. After contact with the flame, only the surface layer of the fiber sheet material on the flame side was carbonized, and there was no deformation or major change in appearance on the non-flame side or at the joint interface, demonstrating sufficient flame blocking and flame resistance.
[0048] [Example 2] The weight ratio of the stretched PPS fiber yarn and the flame-resistant yarn in the nonwoven fabric of Example 1 was changed to 90:10, and the basis weight was 100 g / m 2A nonwoven fabric having a thickness of 1.53 mm was obtained. The nonwoven fabric obtained and the glass fiber reinforced PPS resin were integrated by hot press bonding in the same manner as in Example 1 to obtain a flame-resistant laminated molded product. The obtained flame-resistant laminated molded product had a fusion compatible layer having a thickness of 67 μm and a bonding strength of 3.9 kg / cm in a tensile test. 2 The failure mode was favorable, with failure of the nonwoven fabric base material. In the flame resistance test, there was no penetration of the flame or ignition of the glass fiber reinforced PPS resin, and the maximum temperature at the center of the surface of the glass fiber reinforced PPS resin on the non-flame side was 221°C. After contact with the flame, only the surface layer of the fiber sheet material on the flame side was carbonized, and there was no deformation or major change in appearance on the non-flame side or at the joint interface, demonstrating sufficient flame blocking and flame resistance.
[0049] [Example 3] The weight ratio of the stretched PPS fiber yarn and the flame-resistant yarn in the nonwoven fabric of Example 1 was changed to 10:90, and the basis weight was 100 g / m 2 A nonwoven fabric having a thickness of 1.63 mm was obtained. The nonwoven fabric obtained and glass fiber reinforced PPS resin were integrated by hot press bonding in the same manner as in Example 1 to obtain a flame-resistant laminated molding. The obtained flame-resistant laminated molding had a fusion compatible layer thickness of 33 μm and a bonding strength of 2.3 kg / cm in a tensile test. 2 The failure mode was favorable, with failure of the nonwoven fabric base material. In the flame resistance test, there was no penetration of the flame or ignition of the glass fiber reinforced PPS resin, and the maximum temperature at the center of the surface of the glass fiber reinforced PPS resin on the non-flame side was 208°C. After contact with the flame, only the surface layer of the fiber sheet material on the flame side was carbonized, and there was no deformation or major change in appearance on the non-flame side or at the joint interface, demonstrating sufficient flame blocking and flame resistance.
[0050] [Example 4] As the fiber sheet material of Example 1, carbon fiber (Toray Industries, Inc., "TORAYCA" (registered trademark) with a diameter of 30 microns cut to 51 mm (thermal conductivity 8.4 W / m K)) was used instead of the flame-resistant yarn, and the ratio of stretched PPS fiber to carbon fiber was set to 60:40, with a basis weight of 100 g / m 2A nonwoven fabric having a thickness of 1.89 mm was obtained. The nonwoven fabric obtained and the glass fiber reinforced PPS resin were integrated by hot press bonding in the same manner as in Example 1 to obtain a laminated molded product. The thickness of the fused compatible layer of the obtained laminated molded product was 26 μm, and the bonding strength in a tensile test was 4.0 kg / cm. 2 The failure mode was favorable, with failure of the nonwoven fabric matrix. In the flame resistance test, there was no penetration of the flame or ignition of the glass fiber reinforced PPS resin, but the maximum temperature at the center of the surface of the glass fiber reinforced PPS resin on the side opposite the flame was 270°C. After exposure to flame, significant carbonization and foaming were observed on the surface of the fiber sheet material on the flame side, the side opposite the flame, and at the joint interface, and the deformation of the laminated molded product was 20 mm or more.
[0051] [Example 5] A flame-resistant laminated molding was obtained by using a glass-fiber-reinforced, flame-retardant PBT resin ("Trecon" (registered trademark) product number 1184G-A30N, manufactured by Toray Industries, Inc.) instead of the glass-fiber-reinforced PPS resin of Example 1. The LOI value of this PBT resin was 32. The injection molding temperature conditions during the production of the laminated molding were changed to a cylinder temperature of 260°C and a mold temperature of 80°C. The temperature conditions during the hot press were changed to 260°C, and the other conditions were the same as in Example 1. The obtained flame-resistant laminated molding had a fusion-compatible layer thickness of 0 μm, and the nonwoven fabric was simply impregnated with the resin. The bonding strength in the tensile test was 1.5 kg / cm. 2 The destruction mode was at the bonding interface. In the flame resistance test, although the flame did not penetrate, a flame ignited in the glass fiber reinforced flame retardant PBT resin part at the end of the laminated molded body, but it self-extinguished after the flame contact was stopped. The maximum temperature at the center of the glass fiber reinforced flame retardant PBT resin surface on the non-flame side was 190°C. After the flame contact, only the surface layer of the fiber sheet material on the flame contact side was carbonized, but a distortion deformation of about 1mm in height was observed on the non-flame contact side. After the flame contact, only the surface layer of the fiber sheet material on the flame contact side was carbonized, and there was no major deformation or major change in appearance on the non-flame contact side or at the bonding interface, indicating sufficient flame blocking and flame resistance.
[0052] [Example 6] As the fiber sheet material of Example 1, 100% flame-resistant yarn was used and the basis weight was 100 g / m 2A nonwoven fabric having a thickness of 2.02 mm was obtained. The nonwoven fabric obtained and the glass fiber reinforced PPS resin were integrated by hot press bonding in the same manner as in Example 1 to obtain a laminated molded product. The obtained flame-resistant laminated molded product had a fusion compatible layer thickness of 0 μm, and the nonwoven fabric was simply impregnated with the resin. The bonding strength in a tensile test was 1.5 kg / cm 2 The failure mode was at the bonded interface. In the flame resistance test, there was no penetration of flame or ignition of the glass fiber reinforced PPS resin, but the maximum temperature at the center of the surface of the glass fiber reinforced PPS resin on the non-flame side was 212°C. After contact with flame, the fiber sheet material on the flame side only had carbonized on the surface, and there was no deformation or major change in appearance on the non-flame side or at the bonded interface, indicating sufficient flame blocking and flame resistance.
[0053] [Comparative Example 1] A laminated molded product was obtained by using glass fiber reinforced polyamide 6 resin ("Amilan" (registered trademark) manufactured by Toray Industries, Inc., product number CM1011G-30B2) instead of the glass fiber reinforced PPS resin of Example 1. The LOI value of this polyamide resin was 24. The injection molding temperature conditions when producing the laminated molded product were changed to a cylinder temperature of 260°C and a mold temperature of 80°C. The temperature conditions during hot pressing were changed to 260°C, and the other conditions were the same as in Example 1. The thickness of the fused compatible layer of the obtained laminated molded product was 0 μm, and the resin was simply impregnated into the nonwoven fabric. The bonding strength in the tensile test was 1.3 kg / cm 2 The destruction mode was at the bonding interface. In the flame resistance test, although the flame did not penetrate, a flame ignited in the glass fiber reinforced polyamide 6 resin part at the end of the laminated molded body, and the flame did not self-extinguish for about 10 seconds after the flame contact had stopped. The maximum temperature at the center of the glass fiber reinforced polyamide 6 resin surface on the side opposite the flame was 198°C. After the flame contact, only the surface layer of the fiber sheet material on the flame contact side was carbonized, but a distortion deformation of about 1 mm in height was observed on the side opposite the flame.
[0054] [Table 1] [Industrial Applicability]
[0055] The flame-resistant laminated molding according to the present invention has excellent flame-shielding and flame-resistance properties even when the fiber sheet material side comes into contact with a flame, and therefore can maintain its shape and characteristics, and is applicable to the fields of housing facilities, aircraft, automobiles, etc. In particular, it is suitable for use in battery module loading packs that are installed in xEV automobiles and for which flame-resistance standards are set by national regulations from the viewpoint of safety. [Explanation of symbols]
[0056] 1, 3 Fiber sheet material 2, 4 Thermoplastic resin C 5 Battery module loading pack 6 Battery Module 7. Flame-resistant laminated molding
Claims
1. A flame-resistant laminated molded body, in which one surface of a fiber sheet material containing at least non-melting fiber A and thermoplastic fiber B is exposed to the outside of the molded body, and at least a portion of the other surface side is joined to thermoplastic resin C which constitutes the molded body and is injection molded, wherein the thermoplastic fiber B is polyphenylene sulfide fiber, the thermoplastic resin C is polyphenylene sulfide resin, the thermal conductivity of the non-melting fiber A in accordance with ISO22007-3 (2008) is 0.060 W / m K or less, the fiber sheet material containing the non-melting fiber A and the thermoplastic fiber B is heat-fused to the thermoplastic resin C, and the thickness of the fused compatible layer between the thermoplastic fiber B and the thermoplastic resin C is 10 μm or more.
2. 2. The flame-resistant laminate according to claim 1, wherein the content of the non-melting fiber A in the fiber sheet material is 15 to 80% by weight.
3. 3. The flame-resistant laminate according to claim 1, wherein the content of said thermoplastic fiber B in said fiber sheet material is 20 to 85% by weight.
4. 4. The flame-resistant laminate according to claim 1, wherein the fiber sheet material contains 20% by weight or less of fibers D other than the non-melting fibers A and the thermoplastic fibers B.
5. The flame-resistant laminate according to any one of claims 1 to 4, wherein the non-melting fiber A is a flame-resistant fiber or a meta-aramid fiber.
6. The flame-resistant laminate according to any one of claims 1 to 5, wherein the thermoplastic fiber B has an LOI value according to JIS K 7201-2 (2007) of 25 or more.
7. The flame-resistant laminate according to any one of claims 1 to 6, wherein the thermoplastic fiber B is a fiber containing 15% by weight or more of sulfur atoms.
8. The flame-resistant laminate according to any one of claims 1 to 7, wherein the thermoplastic resin C has an LOI value according to JIS K 7201-2 (2007) of 25 or more.
9. The flame-resistant laminate according to any one of claims 1 to 8, wherein a portion of the thermoplastic fiber B and a portion of the thermoplastic resin C are fused to each other.
10. The thermoplastic fiber B and the thermoplastic resin C are made of the same resin, and the bonding strength between the fiber sheet material containing the non-melting fiber A and the thermoplastic fiber B and the thermoplastic resin C is 1.5 kg / cm 2 The flame-resistant laminated molding according to any one of claims 1 to 9.
11. The flame-resistant laminated molding according to any one of claims 1 to 10, wherein the fiber sheet material containing the non-melting fiber A and the thermoplastic fiber B is configured to be a fiber sheet material capable of exhibiting flame-proofing properties by forming a membrane between the non-melting fiber A by melting the thermoplastic fiber B and carbonizing the membrane under the condition that oxygen is blocked.
12. The flame-resistant laminate according to any one of claims 1 to 11, wherein the fiber sheet material containing the non-melting fibers A is partially present on a surface of the thermoplastic resin C.
Citation Information
Patent Citations
laminate
JP1991096341A
Sound-absorbing material
JP2000008260A
Flame-retardant fiber sheet
JP2013169996A
Fiber-reinforced plastic molded body and base material for fiber-reinforced plastic molded body
JP2017114107A
Nonwoven fabric sheet
WO2019188276A1